Genome‐wide association mapping of ethanol sensitivity in the Diversity Outbred mouse population. (17th April 2022) - Parker, Clarissa C.; Philip, Vivek M.; Gatti, Daniel M.; Kasparek, Steven; Kreuzman, Andrew M.; Kuffler, Lauren; Mansky, Benjamin; Masneuf, Sophie; Sharif, Kayvon; Sluys, Erica; Taterra, Dominik; Taylor, Walter M.; et al.
Abstract: Background: A strong predictor for the development of alcohol use disorder (AUD) is altered sensitivity to the intoxicating effects of alcohol. Individual differences in the initial sensitivity to alcohol are controlled in part by genetic factors. Mice offer a powerful tool to elucidate the genetic basis of behavioral and physiological traits relevant to AUD, but conventional experimental crosses have only been able to identify large chromosomal regions rather than specific genes. Genetically diverse, highly recombinant mouse populations make it possible to observe a wider range of phenotypic variation, offer greater mapping precision, and thus increase the potential for efficient gene identification. Methods: We have taken advantage of the Diversity Outbred (DO) mouse population to identify and precisely map quantitative trait loci (QTL) associated with ethanol sensitivity. We phenotyped 798 male J:DO mice for three measures of ethanol sensitivity: ataxia, hypothermia, and loss of the righting response. We used high‐density MegaMUGA and GigaMUGA to obtain genotypes ranging from 77, 808 to 143, 259 SNPs. We also performed RNA sequencing in striatum to map expression QTLs and identify gene expression–trait correlations. We then applied a systems genetic strategy to identify narrow QTLs and construct the network of correlations that exists between DNA sequence, gene expression values, and ethanol‐related phenotypes to prioritize our list of positional candidate genes. Results: We observed large amounts of phenotypic variation with the DO population and identified suggestive and significant QTLs associated with ethanol sensitivity on chromosomes 1, 2, and 16. The implicated regions were narrow (4.5–6.9 Mb in size) and each QTL explained 4–5% of the variance. Conclusions: Our results can be used to identify alleles that contribute to AUD in humans, elucidate causative biological mechanisms, or assist in the development of novel therapeutic interventions. Abstract : Highly recombinant and genetically diverse mice can help address limitations faced by human alcohol use disorder (AUD) genome‐wide association studies (GWAS). We phenotyped the diversity outbred (DO) mouse population for variation in three ethanol‐sensitivity endophenotypes, performed high‐resolution mapping of quantitative trait loci (QTLs) underlying response to ethanol, mapped expression QTLs, and used a series of bioinformatics approaches to integrate results across endophenotypes, expression data, and species in order to parse among the positional candidate genes within our QTL intervals.